Endovascular repair of acute type B thoracic aortic dissection - Le Huu, Alice; Preventza, Ourania (Annals of Cardiothoracic Surgery, 2021)
Approximately one-third of patients with acute Stanford type B or DeBakey type III aortic dissection (TBAD) will develop complications, including persistent symptoms, malperfusion, enlarging aneurysms and impending rupture. In these cases, TBAD becomes a surgical emergency that requires endovascular intervention to complement the medical therapy. The immediate goal of endovascular therapy is to reestablish flow to the true lumen, stabilize the aneurysm and prevent rupture. Long-term goals are the remodeling of the descending thoracic aorta and the prevention of further surgeries in the thoracoabdominal aorta. In this report, we describe our step-by-step endovascular approach to TBAD repair.